ZnO nanorod multilayer film prepared by hydrothermal growth and its application in dye sensitised solar cells. (July 2015) - Liu, R.; Xu, Y.; Li, Z.; Wang, X.; Zhang, J.; Ye, C.; Wang, H.
Abstract : ZnO nanorod multilayer film was hydrothermal fabricated on fluorine-doped SnO2 -coated glass (FTO) substrate using the sol–gel method from a ZnO seed layer. Such a multilayer film has micrometre scale arms linking with ZnO nanorod arrays vertical to the FTO substrate. It provides a large surface area for dye adsorption and a rapid pathway for electron transport along the nanorod channel. The sensitised solar cell based on the optimised ZnO nanorod multilayer film with thickness of 56.7 μm reaches a power conversion efficiency (PCE) of 1.8%.